2011
DOI: 10.1080/08120099.2011.543151
|View full text |Cite
|
Sign up to set email alerts
|

Crustal architecture of central Victoria: results from the 2006 deep crustal reflection seismic survey

Abstract: A *400 km long deep crustal reflection seismic survey was acquired in central Victoria, Australia, in 2006. It has provided information on crustal architecture across the western Lachlan Orogen and has greatly added to the understanding of the tectonic evolution. The east-dipping Moyston Fault is confirmed as the suture between the Delamerian and western Lachlan Orogens, and is shown to extend down to the Moho. The Avoca Fault, the boundary between the Stawell and Bendigo Zones, is a west-dipping listric reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 105 publications
(220 reference statements)
3
100
0
Order By: Relevance
“…14). Its trapezoid geometry is similar to that of the Selwyn Block in central Victoria, as imaged in recent seismic profiles Cayley et al, 2011); and it could have acted as a buttress, also similar to that proposed for the Selwyn Block (Cayley et al, 2002).…”
Section: Lower Crustal Elementsmentioning
confidence: 89%
“…14). Its trapezoid geometry is similar to that of the Selwyn Block in central Victoria, as imaged in recent seismic profiles Cayley et al, 2011); and it could have acted as a buttress, also similar to that proposed for the Selwyn Block (Cayley et al, 2002).…”
Section: Lower Crustal Elementsmentioning
confidence: 89%
“…To the east, the VT2 segment of the 2006 Victorian transect in the western Lachlan Fold Belt shows clear mid crustal reflections, which are inferred to be associated with the Proterozoic Selwyn Block (Cayley et al [29]). The reflection section is of high quality with clear thrust connection to surface ophiolites at CDP 8200 ( Fig.…”
Section: Line 06-vt2mentioning
confidence: 96%
“…Limestones in the west of the region had presented considerable problems with the older low fold procedures, but very high quality data was obtained with the vibrator sources in 2009. To the west the main reflection profile SD1 linked to the 2006 Victorian transect (Cayley et al [29]). …”
Section: Lines 09-sd1 09-sd2mentioning
confidence: 99%
“…One example of this was the Western Lachlan Fold Belt in Victoria, where more recent seismic surveys have now confirmed the presence of extended Proterozoic basement underlying the orogen at depth (e.g. Willman et al 2010;Cayley et al 2011) Consistent with these observations, recent lithosphericmantle focused, integrated geophysical and geochemical studies have shown that juvenile arc-related lithosphere is, perhaps surprisingly, not a major component of accretionary orogens Belousova et al 2010;Griffin et al 2011). The reason for this relates to the fundamental processes of continental lithosphere formation, as summarised by Griffin et al (2009).…”
Section: Accretionary Orogensmentioning
confidence: 99%
“…4 Schematic illustration of the conjunction of three independent parameters required to form a world-class gold deposit (of any deposit type) within an accretionary orogen Western Lachlan Fold Block of Victoria. These deposits are located above the inferred margins of the Selwyn Block, an underlying older basement domain that occurs locally within the orogen (Miller et al 2006;Cayley et al 2011). …”
Section: Fertile Upper Mantle Source Regionmentioning
confidence: 99%